Destination memory: Memory associated with social interactions - El Haj, Mohamad (Frontiers in Psychology, 2023)
Within the field of memory research, studies on destination memory (e.g., the ability to remember to whom information was previously told) show how it is closely associated with social cognition. The present review thus summarizes the literature on destination memory and demonstrates how it involves social interaction. It offers a comprehensive picture of the many factors that may influence destination memory and distinguishes factors related to the recipient (e.g., familiarity, emotional states, distinctiveness/attractiveness) and sender of information (e.g., the sender’s extroversion) in social communications. It suggests that destination memory involves the ability of the sender to infer the cognitive/affective state of the recipient and to attribute the output message to a recipient-related stereotype. Extrovert senders may also easily remember the destination as they typically value social communication, public sharing and processing of social information. Destination memory also involves features such as familiarity, age, emotional state, distinctiveness and attractiveness of the recipient. By offering a comprehensive framework of how destination memory functions in everyday life interactions, the present review shows how destination memory is intimately associated with communicative efficacy and social interactions.